Cowpox Virus Transmission from Rats to Monkeys, the Netherlands - Martina, Byron E.E. (Centers for Disease Control and Prevention, 2006)
We report an outbreak of cowpox virus among monkeys at a sanctuary for exotic animals. Serologic analysis and polymerase chain reaction were performed on blood and swab samples from different rodent species trapped at the sanctuary during the outbreak. Sequence comparison and serologic results showed that brown rats (Rattus norvegicus) transmitted the virus to monkeys.